Worldwide productivity and research trend of publications concerning SIAD: a bibliometric study - Wei, Xiaodan; Pan, Weiyuan; Lun, Shaocong; Wu, Yuexuan; Chen, Yushi; Feng, Taoshan; Liu, Meilian; Chen, Xiaoming (Frontiers in Endocrinology, 2024)
Background Syndrome of inappropriate antidiuretic(SIAD) occurs secondary to various diseases, which is characterised by hypotonic hyponatremia and impaired urinary diluting capacity. Research on SIAD in both domestic and international contexts has a long history. This study objectively and comprehensively analyses the research trends, hotspots and development of SIAD research of the past 20 years using the method of bibliometric analysis. Methods The 2003–2022 data in the Web of Science Core Collection database were searched. The Bibliometrix software package, VOSviewer and CiteSpace were used to mine, extract and visualise the retrieved literature, and the generated maps were used in analysing the main topics and trends in the field of SIAD research. Results A total of 1215 articles published in 623 journals were included in the analysis, with a total of 18,886 citations. Results showed that the research output on SIAD has continuously increased in the past 20 years, and the United States had the highest number of publications and citations. Keywords with the highest burst strength in recent years were the most mentioned keywords, in addition to the search terms ‘hyponatremia’, ‘covid-19’, and ‘mortality’. Thus, the relationship among SIAD, covid-19 and mortality may become research frontiers and trends. Fifteen milestone articles were identified through co-citation analysis, which mainly focused on the pathophysiology and treatment of SIAD. Conclusion Based on bibliometric analysis and knowledge mapping, this study summarises development trends in the field of SIAD research, providing references for current and future research into SIAD.